Aligning Education Policies Using Data to Improve Literacy, Numeracy, and Learning Outcomes - Nurhaeni Sikki; Novi Anggraini; Iqbal Hidayatullah; Aldersi Redo Anryat Sembiring; Billy Hermanto; Irvinni Rizky Ramadanty (Ambarsa : Jurnal Pendidikan Islam, 2026)
This study aims to evaluate the effectiveness of central government policies in shaping educational outcomes, particularly as reflected in the results of the 2024-2025 Education Report Card. By focusing on key indicators such as literacy, numeracy, and overall learning quality, this research seeks to understand not only improvements in student performance but also the broader implications of policy implementation across different educational levels. Using a qualitative approach, the study analyzes secondary data to identify trends and patterns that reveal both the successes and shortcomings of current educational strategies. The findings indicate notable improvements in primary school numeracy, which increased by 7.95 points, and literacy, which rose by 1.65 points. However, the quality of learning, as measured by classroom practices and pedagogical effectiveness, experienced a decline of 2.23 points. At the junior high school level, a similar trend emerges: numeracy scores improved by 2.77 points, while literacy slightly decreased by 0.18 points, and learning quality dropped by 0.75 points. These results suggest that while students are achieving higher scores in measurable areas such as literacy and numeracy, these gains are not translating into improved educational experiences, likely due to the prevalence of “teaching to the test” strategies. Consequently, the region continues to rank among the lowest nationally in terms of holistic educational quality. Future research should explore more structured clinical mentoring models and emphasize continuous monitoring of regional education policies to ensure sustainable and meaningful improvements in educational quality.